Epidemiology and characterisation of major bovine mastitis pathogens in selected dairy herds of Peninsular Malaysia - Ali, Bashir (2020)
Bovine mastitis is a costly endemic disease in dairy cows. In recent times, there was need by Malaysian government to boost local dairy production in order to cater for local consumption. Mastitis research; involving the epidemiology and antimicrobial resistance profile studies as well as identification of vaccine candidate targets against major mastitis pathogens, is central in enhancing dairy production. This research was aimed at studying the epidemiology of bovine mastitis pathogens from selected states of Malaysia, molecular characterise the major pathogens implicated, and identify vaccine candidate target of selected mastitis pathogens. The objectives of the study were; to determine the bacterial pathogens associated with bovine intramammary infections from selected states of Malaysia and antimicrobial resistance pattern of most prevalent pathogens; to determine the prevalence of subclinical mastitis and its associated risk factors from selected states of Malaysia; to characterise Staphylococcus aureus isolates as the most prevalent implicated pathogens associated with mastitis in selected states of Malaysia; and to identify immunogenic targets for development of candidate vaccines against selected mastitis pathogens by reverse vaccinology approach. Total of 1945 quarter samples from 517 cows across 33 farms were collected using a cross-sectional study design. All samples were subjected for California mastitis test (CMT). Isolation and identification of mastitis pathogens was carried out based on standard bacteriological procedures for all CMT positive samples. Antimicrobial resistance profile of selected most prevalent pathogens associated with mastitis was conducted by disk diffusion technique. Risk factors associated with subclinical mastitis were analysed. Staphylococcus aureus isolates implicated in mastitis were characterised by multi locus sequence typing (MLST). Immunogenic proteins as targets for candidate vaccine development against three mastitis isolates namely; Staphylococcus aureus, Escherichia coli and Streptococcus agalactiae were identified by reverse vaccinology approach. The overall culture proportion positive was recorded as 68.3% (n=503/736, CI= 64.9-71.6). The respective states’ culture proportion positive was 68.3% (n=71/104, CI= 58.9-76.4), 60.5% (184/304, CI= 54.6-65.8), 58.4% (n=94/161, CI= 50-65.6), 100% (n=75/75, CI= 93.9-100), and 85.9% (n=79/92, CI= 73.8-89.8) for Pahang, Perak, Selangor, Negeri Sembilan and Johor respectively. Significant difference was observed between states’ culture prevalence (χ2=63.8, P<0.001). Mastitis risk factors such as breed, age, parity, lactation stage, teat lesion score, were found to be statistically associated with occurrence of mastitis (P < 0.05). The most prevalent isolates identified were non-aureus staphylococci (NAS) 39.5%, S. aureus 13.1%, K. pneumoniae 6.5%, S. agalactiae 4.8%, S. uberis 4.3% and E. coli 2.6%. Resistance profile of K. pneumoniae isolates against ampicillin and Penicillin G were 70.4% and 88.9% respectively while that of Actinobacter spp. against chloramphenicol and streptomycin were 71.4% and 35.7% respectively. For S. uberis isolates, 66.7% and 73.3% have shown resistance to tetracycline and streptomycin respectively. The multi-locus sequence and typing (MLST) identified six sequence types (STs) of S. aureus isolates. The ST97 was the most prevalent (40%) followed with ST1 (20%). The rest belong to ST1496 (10%), ST4427 (10%), ST221 (10%) and ST2125 (10%). A total of 18 immunogenic proteins comprising of surface exposed and secretory components were identified as targets for candidate vaccine against three major mastitis pathogens (S aureus, S. agalactiae and E. coli). Their conserved and consensus epitopes for B-cells and T-cells were identified. These composed of six from E. coli, three from S. aureus and nine from S. agalactiae. In conclusion, the prevalence of mastitis, the distribution and composition of mastitis associated pathogens as well as the key predisposing factors have been established. The molecular characteristics of S. aureus as the most prevalent mastitis associated pathogen were uncovered, targets for potential vaccine candidates against major mastitis pathogens were determined. These outcomes would assist in formulating policies and designing of mastitis control and preventive programs with the view to curbing the losses and costs incurred due to mastitis. This would ultimately help in meeting up the target for dairy milk self-sufficiency and improve the economies of dairy farmers in Malaysia.